Conversion of non-van der Waals VO2 solid to 2D ferromagnet by CO2-induced phase engineering. (October 2021) - Zhou, Yannan; Yan, Pengfei; Zhang, Suoying; Ma, Chao; Ge, Tianpei; Zheng, Xiaoli; Zhang, Li; Jiang, Jingyun; Shen, Yonglong; Chen, Jun; Xu, Qun
Highlights: A CO2 -induced phase engineering strategy is proposed to convert the non-van der Waals VO2 bulk to 2D ferromagnet. Supercritical CO2 liquid can generate a strong force field to "plasticize" VO2 bulk at the architectural scale. The detailed mechanisms of 3D-to-2D transformation and metastable phase-generations are illustrated by DFT calculations. This strategy can activate the room-temperature ferromagnetism in non-magnetic VO2 . Graphical Abstract: ga1 Abstract: Two-dimensional (2D) ferromagnetic semiconductors that combine ferromagnetic order with desirable physical attributes could find transformative applications in atomically-thin magneto-optical and magnetoelectric devices. The mainstream strategies of creating magnetic moments in 2D materials are introducing charge carriers. Here we introduce a CO2 -induced phase engineering strategy that achieves 2D ferromagnet via the transformation of non-van der Waals (non-vdW) VO2 solid to 2D defective structure with identified metastable phases. Our approach requires only exposing the structure to supercritical CO2 liquid that is able to first infiltrate and swell the material at the molecular scale, and then "plasticize" VO2 solid at the architectural scale to form a 2D defective network that 'lock' the metastable phases into a new topological structure, which would lead to a significantly enhanced ferromagnetic response. We attribute the phase transformation to the CO2 pressure-induced selective cleavage of covalent bond.